A study on the perception on the interior aesthetics of CASAA Food Center of selected UP College students - Pascual, Erlynne D.; Faustino, Johanna Victoria Acab (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT The College of Science and Alumni Association (CASAA) Food Center is one of the most visited canteens in UP Diliman Campus. Being a popular food establishment, does it serve the purpose of offering an appropriate, satisfying and memorable visual experience to its consumers? This led the researcher to evaluate the perception of selected UP college students on the interior aesthetics of CASAA Food Center and how these affect the students‟ dining experience. Employing a qualitative research design, specifically, the descriptive method, observations and photo documentation were performed and survey were distributed to 50 respondents currently enrolled in the University from different disciplines and year levels. By utilizing a combination of convenience and purposive sampling design, ten respondents for each year level from first to fifth year were chosen as respondents with both genders equally represented in the study. Theories of Perception and Principles of Design were used to assess the respondents‟ perceptions and to know their needs and concerns as consumers. This study has identified significant visual elements that contribute to the aesthetic quality of the facility such as color, lighting, display, cleanliness and layout. It was found out that color and cleanliness are the most important visual elements for the respondents of this study. Results showed that the interior aesthetics of the CASAA Food Center play an important role to the students‟ wellness because these influence and enhance their dining experience resulting to a good mental and physical condition. However, the students found the CASAA‟s interior not appealing. Based on the respondents‟ comments and suggestions, CASAA‟s interior aesthetics should be improved. Since the scope of the study focused only on the visual elements of the CASAA, the researcher recommends that further research be conducted including aspects concerning ventilation, sanitation and space planning.
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: School lunchrooms, cafeterias, etc. -- Philippines -- Interior decoration